CHROMOSOME COUNT ON YOUNG ANTHER OF BANANA MALE BUD USING EZYMATIC MACERATION AND DAPI STAINING IN SLIDE PREPARATION - Fajarudin Ahmad; Yuyu Suryasari Poerba (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Chromosome counting is the basis in describing the chromosomes number of organism that might useful for genetic study and classification. In banana studies, the root tip with a combination of non-fluorescent staining methods such as carmine or orcein and squash is the most common material for chromosome counting. In this study, we presented the usefulness of young anther of banana male bud with enzymatic maceration method for cell spreading and 4,6-diamino-2-phenyl-indole (DAPI) for staining agent to get a satisfying chromosomes image at metaphase for mitotic study of diploid and tetraploid bananas. The principle of this study is fixation using ethanol:acetic acid (3:1), enzymatic digestion, maceration and staining using DAPI. Our result showed that this method can provide well spread cells with intensely contrast of chromosomes images that satisfying for chromosome counting.